Disparities in Familiarity with Developmental Disabilities among Low-Income Parents - Zuckerman, Katharine E. (Acad Pediatr, 2018)
OBJECTIVE: Parent knowledge about developmental disabilities (DDs) may facilitate access to DD care; however, parents may vary in their knowledge and familiarity with common DDs. This study aimed to assess racial/ethnic and language differences in low-income families’ familiarity, knowledge, and personal experience with DDs. METHODS: We conducted a child development survey among 539 low-income parents of young children attending visits at the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC), in six Oregon counties in 2015. Survey items assessed parent familiarity with early signs of DDs, self-reported knowledge about DDs, and personal experience with a friend or family member with a DD. Bivariable and multivariable analyses assessed differences in outcomes among non-Latino white [white], Latino-English proficient [Latino-EP], Latino-limited English proficient [Latino-LEP], and non-Latino other race English proficient [other race] parents. RESULTS: Overall, parent participants correctly identified 64.7% of early signs of DDs. White parents correctly identified the earliest signs, even after adjustment for socio-demographic factors. Latino-LEP, Latino-EP and other race parents were less likely to have heard of prevalent DDs such as ADHD and autism, and were less likely to have a friend or family member with a DD compared to white parents. CONCLUSIONS: Low-income Latino-LEP and other race parents have less familiarity or personal experience with DDs, and are less aware of DD early signs compared to low-income white parents. Study findings suggest that interventions to reduce disparities in DD diagnosis and treatment should include increasing information transfer to parents in racial/ethnic and language minority communities. WHAT’S NEW: Low-income racial/ethnic minority parents, and particularly Latinos parents with limited English proficiency, have less familiarity or personal experience with DDs, and are less aware of DD early signs compared to low-income white parents.